The Information Systems at Irfan Jaya Stores Using the Rational Unified Process Method - Syah, Muhammad Irfan Rasnan; Lukman, Lukman (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Irfan Jaya's shop is a shop that sells Papuan-patterned clothes, bags, and sweaters since 2011. However, as the shop's business grew, there were several problems experienced in its business processes, such as information and store promotion systems which were only limited to shop banners. Another problem faced by the owner is the collection of goods and sales history is relatively long because they are still doing manual recording on the book. Based on the problems that occur, it is necessary to create a system such as an online shop that can facilitate the owner in managing and controlling his business. The purpose of this study was to design and determine the system requirements of the Irfan Jaya store using the Rational Unified Process method. the software is programmed using the PHP programming language and the implementation of the user interface display uses HTML and CSS. The software is built based on a website, with the hope that the device will be a solution to existing problems and able to simplify the business processes that run at the Irfan Jaya store. The results of this study are twofold. First, the system architecture design is at the inception and elaboration stages. Second, system implementation and testing at the construction and transition stages.